Y+3(y-6)=4y+2

Simple and best practice solution for Y+3(y-6)=4y+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y+3(y-6)=4y+2 equation:


Simplifying
Y + 3(y + -6) = 4y + 2

Reorder the terms:
Y + 3(-6 + y) = 4y + 2
Y + (-6 * 3 + y * 3) = 4y + 2
Y + (-18 + 3y) = 4y + 2

Reorder the terms:
-18 + Y + 3y = 4y + 2

Reorder the terms:
-18 + Y + 3y = 2 + 4y

Solving
-18 + Y + 3y = 2 + 4y

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + Y + 18 + 3y = 2 + 18 + 4y

Reorder the terms:
-18 + 18 + Y + 3y = 2 + 18 + 4y

Combine like terms: -18 + 18 = 0
0 + Y + 3y = 2 + 18 + 4y
Y + 3y = 2 + 18 + 4y

Combine like terms: 2 + 18 = 20
Y + 3y = 20 + 4y

Add '-3y' to each side of the equation.
Y + 3y + -3y = 20 + 4y + -3y

Combine like terms: 3y + -3y = 0
Y + 0 = 20 + 4y + -3y
Y = 20 + 4y + -3y

Combine like terms: 4y + -3y = 1y
Y = 20 + 1y

Simplifying
Y = 20 + 1y

See similar equations:

| 8x+-12+2x+2=180 | | 14=-5x+18 | | 12x-5x-3=0 | | 6x-5=9+2 | | 40+4y=y^2+4 | | X+20=9(x-4) | | (12-4i)(3+i)=0 | | c(ad)+x=bd+ad(yz) | | 5x^2=9x-5 | | 360-2x=100 | | 22n=100 | | -10y-3=7y | | (2abc)(-3abc)(-5a)= | | Y=30x+.10 | | -6v+2=1 | | xsquared-7x=-3 | | -6v+2=11 | | 49=2y+17 | | 5(2-4)=30 | | (2abc)(-3abc)(-5)= | | 2x(x+3)-3(2x-3)= | | x^3+-10x+25=0 | | (4v+1)(3+v)=0 | | x^3-10x+26=0 | | 2(x+1)=4x+2 | | 2y-24x=10 | | -2x^2-2x-12=0 | | -2=3y+7 | | -2x-9y=1 | | 36y=1 | | 28+24p=36p | | 2x^3-6x^2-x=0 |

Equations solver categories